Dusty Windows and urban American dreams: Five African journeys toward literacy through participatory research and program development - Lamping, Sally (2007)
When we talk about education, rarely do the faces of this research enter our minds. English as a Second Language (ESL) programs all over the United States, however, are familiar with these new faces. Over the past fifteen years, schools have begun to see a dramatic increase in the number of ESL students whose educations have either never been formal or have been disrupted by wars and socioeconomic issues in their home countries. Among this newer group of students are an increasing number of adult (high school and beyond) African immigrants who come from ethnic groups in which language and literacy have always been oral experiences. As a result, programs are consistently struggling to accommodate them in a country and culture that depends heavily on the printed word. Thus, classrooms and programs must seek new ways to educate them as they learn to read and write in English, without any written literacy in their native languages. This study was a collaborative effort with five African men from oral language backgrounds. It was an investigation into their journeys to read, write, and manage their own cultural transitions in urban America. The study found that their success in this journey relied heavily on the profound role participatory schooling has had in their lives.